Characterization of coding areas of SPGA11B gene in Murrah bulls - Deshmukh, Bharti; Verma, Archana; Gupta, Ishwar Dayal; Kashyap, Neeraj; Mishra, Richa (Buffalo Bulletin, 2022)
The SPAG11 gene is one of pivotal molecules in reproduction as it takes part in spermatozoa maturation, acquiring motility, capacitation, and egg-sperm interaction as well. The current study was aimed to characterize SPAG11 gene in Indian Murrah bulls through direct DNA sequencing approach. Genomic DNA from Murrah animals were isolated from 130 Murrah bulls and amplified using three sets of forward and reverse primers which were based on reference sequence (Genbank accession no. AC_000164.1) of Bos taurus covering entire coding region of SPAG11B gene. The PCR products of 563, 340 and 373, bp covering exons 1 to 3 were subjected to sequencing and subsequently ClustalW analysis revealed the substitution at 34 positions and a single stretch of 22 bp deletion in comparison to the Bos taurus reference sequence. Total seven novel SNPs were observed as two in the coding region and five in 5ˈUTR. However, only one of SNPs resulted in amino acid substitution viz. p.1279 arginine to tryptophan in translated protein in Murrah buffaloes. Sequence alignment and homology across species for the targeted nucleotide sequence of SPAG11 gene in Murrah bulls was done by nucleotide BLAST (NCBI) that showed maximum identity of 97% with mRNA of Bos taurus and Capra hircus followed by 96% homology with Bos indicus and Bison bison and 95% homology with Ovis aries and Bos mutus.